2016
DOI: 10.1103/physrevc.93.024608
|View full text |Cite
|
Sign up to set email alerts
|

Excitation functions of heavy residues produced in theN14+Rh103reaction up to 400 MeV: Analysis of the pre-equilibrium mechanism with the hybrid Monte Carlo simulation model

Abstract: The excitation functions of heavy residues, produced in the interaction of 14 implemented in the recently released ALICE 2014 code. The theory assumes that the dominant pre-equilibrium mechanism includes multi-nucleon and cluster emission in the initial stages of the interaction between the projectile and the target nucleus. Overall, the theoretical predictions provide a satisfactory agreement with the trend of the present experimental results for most of the observed reaction residues. This provides strong e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Results using the KRK level density were somewhat inferior. In another work [6] Here the contribution from breakup and pre-equilibrium are supposed to be small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results using the KRK level density were somewhat inferior. In another work [6] Here the contribution from breakup and pre-equilibrium are supposed to be small.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to understand the pre-equilibrium process in terms of nucleon-nucleon interactions within the target nucleus [1][2][3][4][5][6]. In the last few decades, several quantum mechanical theories have been proposed which can provide a way of calculating cross-sections of pre-equilibrium processes without the uncertainties of semi-classical approximations.…”
Section: Introductionmentioning
confidence: 99%
“…Fermi energy is provided by the two-body interaction between the nucleons of the composite system, and the rearrangement of energy between these nucleons takes place through the coupling between the translational momentum per nucleon of the colliding nuclei with their internal momentum [1]. The particle emissions in the PEQ process play a significant role in enhancing the production of residues in light and heavy-ion reactions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The study gives an encyclopedic idea of those processes that occur during the deexcitation of nonequilibrated hot rotating nuclei created after a projectile-target interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al examined the PEQ emission from the 12 C and 16 O induced reactions on some medium mass targets within ∼7 MeV/nucleon energy range [4]. Acharya et al [7] measured the excitation functions from 14 N+ 103 Rh reaction up to 400 MeV energy and concluded that by including the multinucleon and cluster emissions in initial stages during the PEQ emissions provide satisfactory results with experimental data using Hybrid Monte Carlo simulation(HMS) model. In this series, a study of complete-incomplete fusion (CF-ICF) and PEQ reactions have been carried out using the 12 C+ 197 Au reaction below 10 MeV/nucleon energy [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation